Characterization of sound pressure levels and sound sources in the intensive care unit: a 1 week observational study - Naef, Aileen C.; Knobel, Samuel E. J.; Ruettgers, Nicole; Rossier, Marilyne; Jeitziner, Marie-Madlen; Zante, Bjoern; Müri, René M.; Schefold, Joerg C.; Nef, Tobias; Gerber, Stephan M. (Frontiers in Medicine, 2023)
Background Exposure to elevated sound pressure levels within the intensive care unit is known to negatively affect patient and staff health. In the past, interventions to address this problem have been unsuccessful as there is no conclusive evidence on the severity of each sound source and their role on the overall sound pressure levels. Therefore, the goal of the study was to perform a continuous 1 week recording to characterize the sound pressure levels and identify negative sound sources in this setting. Methods In this prospective, systematic, and quantitative observational study, the sound pressure levels and sound sources were continuously recorded in a mixed medical–surgical intensive care unit over 1 week. Measurements were conducted using four sound level meters and a human observer present in the room noting all sound sources arising from two beds. Results The mean 8 h sound pressure level was significantly higher during the day (52.01 ± 1.75 dBA) and evening (50.92 ± 1.66 dBA) shifts than during the night shift (47.57 ± 2.23; F(2, 19) = 11.80, p < 0.001). No significant difference was found in the maximum and minimum mean 8 h sound pressure levels between the work shifts. However, there was a significant difference between the two beds in the based on location during the day (F(3, 28) = 3.91, p = 0.0189) and evening (F(3, 24) = 5.66, p = 0.00445) shifts. Cleaning of the patient area, admission and discharge activities, and renal interventions (e.g., dialysis) contributed the most to the overall sound pressure levels, with staff talking occurring most frequently. Conclusion Our study was able to identify that continuous maintenance of the patient area, patient admission and discharge, and renal interventions were responsible for the greatest contribution to the sound pressure levels. Moreover, while staff talking was not found to significantly contribute to the sound pressure levels, it was found to be the most frequently occurring activity which may indirectly influence patient wellbeing. Overall, identifying these sound sources can have a meaningful impact on patients and staff by identifying targets for future interventions, thus leading to a healthier environment.